The Analysis Of Students’ Errors for Writing Simple Present Tense in Descriptive Text - Wahyu Satya Gumelar; Bangkit (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2024)
In learning, simple present tense is the basic tense that should be mastered by the student and descriptive is one of the text types uses present tense. Descriptive is used the researcher as the text that let the students apply their writing ability in using present tense. This research paper explores the analysis of students’ errors for writing simple present tense in descriptive text. Therefore, the purpose of this study is to find out the types of error that students made in writing descriptive text and the main factors that causing students errors in writing descriptive text. The research design used case study, with qualitative approach. The participants are 19 students of tenth grade at SMK Harapan 2 Rancaekek. This study used observational checklist, field notes, document analysis, and interview. In interview, the researcher only selected 6 students are divided into 3 categories, namely high achiever, middle achiever, and low achiever. The result of this study showed two points, they are: first, there are three types errors those the students made in writing descriptive text omission, addition, and misformation. The second is main factors that causing students’ errors in writing descriptive text were understanding about grammar exactly in simple present tense, faced difficulties when should write English using tense (present tense) into written and lack vocabularies